Overexpression of Arabidopsis VIT1 increases accumulation of iron in cassava roots and stems. (November 2015) - Narayanan, Narayanan; Beyene, Getu; Chauhan, Raj Deepika; Gaitán-Solis, Eliana; Grusak, Michael A.; Taylor, Nigel; Anderson, Paul
Highlights: AtVIT1 overexpression showed 3–4 times increase in cassava storage root iron concentration. AtVIT1 transgenic cassava plants localize iron in and near the vascular tissues. AtVIT1 transgenic cassava plants have altered expression of genes involved in iron homeostasis. AtVIT1 overexpression indicates a potential strategy for iron biofortification in food crops. Abstract: Iron is extremely abundant in the soil, but its uptake in plants is limited due to low solubility in neutral or alkaline soils. Plants can rely on rhizosphere acidification to increase iron solubility. AtVIT1 was previously found to be involved in mediating vacuolar sequestration of iron, which indicates a potential application for iron biofortification in crop plants. Here, we have overexpressed AtVIT1 in the starchy root crop cassava using a patatin promoter. Under greenhouse conditions, iron levels in mature cassava storage roots showed 3–4 times higher values when compared with wild-type plants. Significantly, the expression of AtVIT1 showed a positive correlation with the increase in iron concentration of storage roots. Conversely, young leaves of AtVIT1 transgenic plants exhibit characteristics of iron deficiency such as interveinal chlorosis of leaves (yellowing) and lower iron concentration when compared with the wild type plants. Interestingly, the AtVIT1 transgenic plants showed 4 and 16 times higher values of iron concentration in the young stem and stem base tissues, respectively. AtVIT1 transgenic plants also showed 2–4 times higher values of iron content when compared with wild-type plants, with altered partitioning of iron between source and sink tissues. These results demonstrate vacuolar iron sequestration as a viable transgenic strategy to biofortify crops and to help eliminate micronutrient malnutrition in at-risk human populations.